Two treatment methods on Ulva prolifera bloom result in distinctively different ecological effects in coastal environment - Dong, Shuhang; Xin, Yu; Liu, Chunying; Xiao, Yanqi; Feng, Xiao; Liu, Tao (Frontiers in Marine Science, 2023)
“Green tides” (Ulva prolifera) have been occurring in the Yellow Sea for more than 10 years, becoming a regular ecological disaster. The largest “green tide” to date, which occurred in 2021, spurred innovation in treatment methods. Unlike traditional harvest- disposal methods, a pre-decomposion method was widely employed, which microbial complex formulation was sprayed on the harvested U. prolifera, and then fermented before disposal into the sea. We hypothesize that there exist significant different ecological effects of these two methods. In order to examine this hypothesis, we run an in-lab incubation of 60 days to simulate the two methods to degrade U. prolifera, with focuses on the degradation ensued impacts on water quality. In the first 20 days, pre-decomposed U. prolifera was completely degraded, accelerating the degradation of U. prolifera by at least 14-fold compared to natural degradation. The large amounts of dissolved organic matter (DOM) released by the pre-decomposed U. prolifera degraded rapidly and posed significant risks of regional hypoxia and acidification. In the final phase, complete degradation of pre-decomposed U. prolifera , interestingly, resulted in a 13% increase in total alkalinity (TA), which was not seen in the naturally degraded ones. Besides, microbial community were significantly affected by both treatment methods. In summary, the two treatment methods had markedly different ecological effects. Pre-decomposing treatment was a more rapid and effective disposal method, but should be used with enough cautiousness.